The significance of the requirement and the rulings attached to it, applied models from the two surahs of Al-Baqarah and An-Nisa (Journal of the College of Basic Education, 2023)
The study (The Sign of Al-Iqtida and related rulings, applied models from the two Suras of Al-Baqarah and An-Nisa) aims to clarify the meaning of the significance, and to clarify a type of its types, which is the indication of Al-Iqtidah, and its ruling, with an explanation of its three types and clarification of the types with the Qur’anic verses and the honorable prophetic hadiths, and then delving into The issue of the generality of the requirement and the statement of the difference of scholars in the event that there is more than one estimation of the text and there is no evidence for the weighting of the estimation, should he take all of them or only one of these estimates, with mentioning the evidence of each group of them, then applied models for the indication of the necessary in the two surahs Al-Baqarah and An-Nisa, in which it becomes clear how The significance of the necessity has a significant impact on clarifying and understanding the text